2012
DOI: 10.1148/radiol.12112007
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Biceps Pulley: Diagnostic Accuracy of MR Arthrography of the Shoulder and Evaluation of Previously Described and New Diagnostic Signs

Abstract: MR arthrography is accurate in the detection of pulley lesions; the displacement sign, nonvisibility or discontinuity of the SGHL, and tendinopathy of the LHBT on oblique sagittal images are the most accurate criteria for the detection of pulley lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 28 publications
8
69
1
1
Order By: Relevance
“…Additional treatment might be necessary for these abnormalities [21,22]. We previously reported the usefulness of radial MRI for the detection of incomplete or complete subscapularis tendon tear [23].…”
Section: Discussionmentioning
confidence: 99%
“…Additional treatment might be necessary for these abnormalities [21,22]. We previously reported the usefulness of radial MRI for the detection of incomplete or complete subscapularis tendon tear [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tears in this ligament may lead to medial subluxation or dislocation of the LHBT. Recently, Schaeffeler et al (28) showed that the prevalence of isolated SGHL tears is 29%.…”
Section: Introductionmentioning
confidence: 99%
“…Biceps pulley lesions can occur due to acute trauma, degenerative changes, repetitive microtrauma, congenital rotator interval defects, or injuries associated with tear in a rotator cuff (13, 24, 28, 29, 30). These lesions are thought to be responsible for medial subluxation of the LHBT, and they may result in loss of function in the shoulder and pain in the anterior shoulder (24, 25, 31).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations